Klein Woordeboek / Little Dictionary - Louw, Phillip Adriaan (Lexikos, 1997)
Bilingual translation dictionaries play an important part in modern user orientated lexicography in South Africa. An affordable bidirectional pocket translation dictionary, such as Klein Woordeboek / Little Dictionary, with English and Afrikaans as language pair, is growing in value as a carrier of necessary everyday linguistic information. At present there are no criteria by which these dictionaries can be judged or that can be of help in their compilation. In this review article an attempt will be made to find typological answers with Klein Woordeboek / Little Dictionary as a guide. This search encompasses traditional and less traditional typological considerations. It focuses on the needs of target users and specifically the role which contextual guidance plays in the furthering of communicative equivalence. Keywords: access structure, addressing structure, article, bidirectional translation dictionary, communicative equivalence, contextual guidance, dual user addressing, equivalent discrimination, explanatory introduction, information density, lemma, lexicography, meaning discrimination, mediostructure, microstructure, pocket translation dictionary, target language synonym paradigm, target user group, theory of organisation, translation equivalent, typology, semantic relations, source and target language polysemy, user addressing, user perspective, user profile